1996
DOI: 10.1073/pnas.93.10.5090
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of spontaneous plant hybrids.

Abstract: Natural hybridization is a relatively common feature of vascular plant species and has been demonstrated to have played an important role in their evolution. Nonetheless, it is not clear whether spontaneous hybridization occurs as a general feature of all plant families and genera or whether certain groups are especially prone to spontaneous hybridization. Therefore, we inspected five modern biosystematic floras to survey the frequency and taxonomic distribution of spontaneous hybrids. We found spontaneous hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
332
0
4

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 371 publications
(347 citation statements)
references
References 9 publications
11
332
0
4
Order By: Relevance
“…Nevertheless, the extensive sharing of chloroplast DNA haplotypes between Q. suber and Q. ilex in some regions has led some authors to hypothesize widespread introgressive hybridization events in the past ( , 2005). Such findings are not incompatible, given that even a low fraction of hybrids can have considerable evolutionary impact because of the cumulative effect of introgression through time (Ellstrand et al, 1996;Mallet, 2005) and the possibility for introgressed genes to become amplified by demographic growth (Currat et al, 2008). In this respect, Ló pez de Heredia et al (2007a) suggested that the acidophilous Q. suber was able to colonize the calcareous area of eastern Iberia (where chloroplast introgression has been reported), thanks to the hybridization with Q. ilex, which is largely indifferent to soil nature.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the extensive sharing of chloroplast DNA haplotypes between Q. suber and Q. ilex in some regions has led some authors to hypothesize widespread introgressive hybridization events in the past ( , 2005). Such findings are not incompatible, given that even a low fraction of hybrids can have considerable evolutionary impact because of the cumulative effect of introgression through time (Ellstrand et al, 1996;Mallet, 2005) and the possibility for introgressed genes to become amplified by demographic growth (Currat et al, 2008). In this respect, Ló pez de Heredia et al (2007a) suggested that the acidophilous Q. suber was able to colonize the calcareous area of eastern Iberia (where chloroplast introgression has been reported), thanks to the hybridization with Q. ilex, which is largely indifferent to soil nature.…”
Section: Discussionmentioning
confidence: 99%
“…Nas espécies sincronopátricas, V. brueggeri e V. hilariana, ambas com diâmetro da corola amplo, a deposição de pólen ocorre na fronte das diversas espécies de beijaflores, promovendo mistura de pólen entre estas espécies. A semelhança nos atributos florais, a sobreposição do período de floração e a proximidade das populações, somadas à mistura de pólen promovida pelos beija-flores entre V. brueggeri e V. hilariana, apoia a hipótese de Chautems (2002) Ellstrand et al (1996) grupos taxonômicos que possuem autocompatibilidade são predispostos à formação e manutenção de híbridos. Embora autocompatibilidade seja característica das espécies da tribo Sinningieae (Clayberg 1968, SanMartin-Gajardo & Sazima 2004), a ausência da formação de frutos no tratamento de autopolinização espontânea indica que a combinação de protandria com hercogamia impede autopolinizações.…”
Section: Discussionunclassified
“…He noted that some taxonomic groups hybridize readily, whereas others do not. These taxonomic correlates of hybridization have been quantified in a recent survey of five biosystematic flora (Ellstrand, Whitkus & Rieseberg, 1996). Focke also suggested that plants with zygomorphic flowers were more likely to hybridize than plants with actinomorphic flowersa tendency that is still recognized (Stebbins, 1957).…”
Section:   mentioning
confidence: 99%